New species of Psychodidae (Diptera) from Australasia, with a checklist of the world species of Bruchomyiinae and Sycoracinae - Curler, Gregory R.; Jacobson, Amanda J. (Zootaxa, 2012)
Adults of one new species of Bruchomyiinae and five new species of Sycoracinae were collected from Australia and New Caledonia, respectively. Nemopalpus glyphanos sp. nov., Sycorax furca sp. nov., S. sinuosa sp. nov., S. spina sp. nov., S. tridentata sp. nov., and S. webbi sp. nov. are described, and Sycorax dispar Satchell from New Zealand is redescribed. A key to males of Sycorax species known to occur in New Caledonia, and a checklist of the world species of Bruchomyiinae and Sycoracinae are provided. Characters of the male genital tract, and relationships among Australasian Bruchomyiinae and Sycoracinae are discussed.